2020
DOI: 10.1093/arclin/acaa006
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Multiple Remote Mild TBIs and Objective Neuropsychological Functioning and Subjective Symptoms in Combat-Exposed Veterans

Abstract: Objective The purpose of this study was to evaluate relationships between multiple mild traumatic brain injuries (mTBIs) and objective and subjective clinical outcomes in a sample of combat-exposed Veterans, adjusting for psychiatric distress and combat exposure. Method In this cross-sectional study, 73 combat-exposed Iraq/Afghanistan Veterans were divided into three groups based on mTBI history: 0 mTBIs (n = 31), 1–2 mTBIs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 62 publications
3
6
2
Order By: Relevance
“…In the case of PCL-5 measures, individuals with multiple deployments showed consistently higher scores (median value of 7), which corresponds with greater PTSD symptomatology (58). Although well-below the threshold for clinical diagnosis (i.e., PCL-5 score ≥ 33), this observation is consistent with a large body of research suggesting a link between multiple deployments, mTBI and increasing vulnerability to developing PTSD and other mental health problems (59,60). These findings should prove useful as researchers work toward developing improved diagnostic tools for distinguishing between the effects of these three conditions that frequently overlap in this population exposed routinely to low-level blast (61,62).…”
Section: Discussionsupporting
confidence: 80%
“…In the case of PCL-5 measures, individuals with multiple deployments showed consistently higher scores (median value of 7), which corresponds with greater PTSD symptomatology (58). Although well-below the threshold for clinical diagnosis (i.e., PCL-5 score ≥ 33), this observation is consistent with a large body of research suggesting a link between multiple deployments, mTBI and increasing vulnerability to developing PTSD and other mental health problems (59,60). These findings should prove useful as researchers work toward developing improved diagnostic tools for distinguishing between the effects of these three conditions that frequently overlap in this population exposed routinely to low-level blast (61,62).…”
Section: Discussionsupporting
confidence: 80%
“…This finding is consistent with previous studies that showed military members and Veterans with multiple, rather than a single, TBI report greater levels of selfreported post-concussive symptoms. 45,46 Unfortunately, the present data did not allow for quantifying and iso lating the cumulative effects of various sources of head injury on post-concussive symptoms -a shortcoming that can be addressed in future studies. An important consideration in interpreting these results is that, aside from greater lifetime exposure to blast, breachers and snipers and controls also diff ered on other relevant dimensions of head injury.…”
Section: Discussionmentioning
confidence: 92%
“…These initiatives and others confirm that Veterans and Service members with mTBI often develop psychiatric disorders, including posttraumatic stress disorder (PTSD), depression, and anxiety (22)(23)(24)(25)(26). Numerous clinical studies described functional impairments in participants exposed to blast(s) years before the onset of debilitating pain, increased headaches, impaired sleep, poor motor skills, and cognitive dysfunction including reduced abilities in intelligence processing speed, visual motor integration and executive functioning (22,24,(26)(27)(28).…”
Section: Characteristics and Impact Of Blast-related Mtbi In Service ...mentioning
confidence: 90%